DETERMINANTS OF POVERTY LEVELS IN MEDAN CITY IN 1998-2021: ERROR CORRECTION MODEL APPROACH - Ramadhan Devan Pratama; Adithiya Rahman Atmaja; Sirojuzilam Hasyim; Irsad; Muhammad Syafii; Wahyu Ario Pratomo; Tetty Yuliaty (Jurnal Ekonomi, 2022)
This research examines the connection between economic growth, education level, government expenditure, and open unemployment in Medan City. This research utilized annual time series data for Medan from 1998 to 2021. This research analysis method employs ECM (Error Correction Model) to comprehend the impact of long-term and short-term predictions processed by Eviews 9 software. According to the research findings, long-term and short-term projections of economic growth, education level, and accessible unemployment have a significant negative impact on poverty levels in the city of Medan. On the other hand, long-term and short-term government spending positively impact the poverty level in Medan City, although the effect is not significant. Based on the result of this research, the Medan City Government should enhance its oversight of the government's budget allocation in the context of reducing poverty in the city of Medan. In addition, the Medan City Government should concentrate its efforts on providing employment opportunities and utilizing competency-based certification and training to decrease unemployment, thereby contributing to reducing poverty in Medan City.